Education policy and intergenerational income mobility: evidence from the Finnish comprehensive school reform - Tuomas Pekkarinen; Roope Uusitalo; Sari Pekkala (Institute for the Study of Labor (IZA), 2006)
Many authors have recently suggested that the heterogeneity in the quality of early education may be one of the key mechanisms underlying the intergenerational persistence of earnings. This paper estimates the effect of a major educational reform on the intergenerational income mobility in Finland. The Finnish comprehensive school reform of 1972-1977 significantly reduced the degree of heterogeneity in the Finnish primary and secondary education. The reform shifted the tracking age in secondary education from age 10 to 16 and imposed a uniform academic curriculum on entire cohorts until the end of lower secondary school. We estimate the effect of the reform on the correlation between son's earnings in 2000 and father's average earnings during 1970-1990 using a representative sample of males born during 1960-1966. The identification strategy relies on a difference-in-differences approach and exploits the fact that the reform was implemented gradually across municipalities during a six-year period. The results indicate that the reform reduced the intergenerational income correlation by seven percentage points.
Keywords: D31; J62; I20; 330; generational mobility; education; comprehensive school reform; Bildungsreform; Bildungspolitik; Erwerbsverlauf; Soziale Mobilität; Overlapping Generations; Finnland